2021
DOI: 10.3390/cells10020357
|View full text |Cite
|
Sign up to set email alerts
|

Tat-Endophilin A1 Fusion Protein Protects Neurons from Ischemic Damage in the Gerbil Hippocampus: A Possible Mechanism of Lipid Peroxidation and Neuroinflammation Mitigation as Well as Synaptic Plasticity

Abstract: The present study explored the effects of endophilin A1 (SH3GL2) against oxidative damage brought about by H2O2 in HT22 cells and ischemic damage induced upon transient forebrain ischemia in gerbils. Tat-SH3GL2 and its control protein (Control-SH3GL2) were synthesized to deliver it to the cells by penetrating the cell membrane and blood–brain barrier. Tat-SH3GL2, but not Control-SH3GL2, could be delivered into HT22 cells in a concentration- and time-dependent manner and the hippocampus 8 h after treatment in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
(96 reference statements)
1
5
0
Order By: Relevance
“…In addition, we confirmed the delivery of 1 mg/kg Tat-MDH1 into the gerbil hippocampus 6 h after ischemia. These results are consistent with previous studies showing that Tat-cargo were efficiently and effectively translocated into HT22 cells and the gerbil hippocampus 24,25,35,36 . In this study, we observed that treatment with H 2 O 2 significantly decreased cell viability, and simultaneous treatment with H 2 O 2 and Tat-MDH1 ameliorated the reduction in cell viability in a concentration-dependent manner, whereas surviving cells were significantly increased after treatment with 4 μM Tat-MDH1 based on 5-CFDA-AM staining.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we confirmed the delivery of 1 mg/kg Tat-MDH1 into the gerbil hippocampus 6 h after ischemia. These results are consistent with previous studies showing that Tat-cargo were efficiently and effectively translocated into HT22 cells and the gerbil hippocampus 24,25,35,36 . In this study, we observed that treatment with H 2 O 2 significantly decreased cell viability, and simultaneous treatment with H 2 O 2 and Tat-MDH1 ameliorated the reduction in cell viability in a concentration-dependent manner, whereas surviving cells were significantly increased after treatment with 4 μM Tat-MDH1 based on 5-CFDA-AM staining.…”
Section: Discussionsupporting
confidence: 93%
“…To elucidate the possible role of 6 mg/kg purpurin against ischemia, we observed the morphology of astrocytes and microglia as well as pro-inflammatory cytokines in the hippocampus because a recent study showed the anti-inflammatory roles of purpurin in RAW 264.7 murine macrophage cells [ 14 ]. The animals were sacrificed 6 h after ischemia to measure IL-1β, IL-6, and TNF-α levels in the hippocampus because these levels are significantly increased in the early period of ischemia [ 29 , 30 , 43 ]. In addition, the IL-1 receptor antagonist showed neuroprotective effects against ischemic damage in rats [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the mechanisms of purpurin’s effects against ischemic damage, animals ( n = 5 in each group) were euthanized with 75 mg/kg alfaxalone and 10 mg/kg xylazine 6 h and 4 days after ischemia/reperfusion, when pro-inflammatory cytokine levels were significantly increased and returned to control levels, respectively [ 29 , 30 ]. In brief, interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α levels were measured in the hippocampus based on comparisons with linear calibration curves generated using IL-1β, IL-6, and TNF-α standard solutions by using their respective enzyme immunoassay kits (BioSource International Inc., Camarillo, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…To elucidate the possible role of 6 mg/kg purpurin against ischemia, we observed the morphology of microglia and pro-in ammatory cytokines in the hippocampus because a recent study showed the antiin ammatory roles of purpurin in RAW 264.7 murine macrophage cells [14]. The animals were sacri ced 6 h after ischemia to measure IL-1β, IL-6, and TNF-α levels in the hippocampus because these levels are signi cantly increased in the early period of ischemia [26,27,39]. In addition, the IL-1 receptor antagonist showed neuroprotective effects against ischemic damage in rats [40].…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the mechanisms of purpurin's effects against ischemic damage, animals (n = 5 in each group) were euthanized with 75 mg/kg alfaxalone and 10 mg/kg xylazine 6 h after ischemia/reperfusion, when pro-in ammatory cytokine levels were signi cantly increased [26,27]. In brief, interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α levels were measured based on comparisons with linear calibration curves generated using IL-1β, IL-6, and TNF-α standard solutions.…”
Section: Measurements Of Pro-in Ammatory Cytokinesmentioning
confidence: 99%